Factors associated with the export of traditional Chinese medicinal products: A stochastic frontier analysis - Ying Chen; Shuduo Zhou; Zhongfei Pei; Weili Zhao; Jian Yang; Yunxuan Hu; Xiangning Feng; Ming Xu (PLoS ONE, 2025)
Background The export of traditional Chinese medicinal products is a pivotal force in enhancing the international recognition of Traditional Chinese Medicine (TCM). From 2013 to 2022, the export trend of traditional Chinese medicinal products demonstrated stable and rapid growth. However, the export structure remained suboptimal, with raw material-based products accounting for a significantly larger proportion than high value-added products. This imbalance has hindered the enhancement of traditional Chinese medicinal value and the potential for branding in the global market. Therefore, an in-depth study of the current status and associated factors of the export is essential to optimize the export structure, adjust export policies, and promote the international trade. Methods We employed joinpoint regression analysis to examine the export value trend of traditional Chinese medicinal products from 2013 to 2022. Subsequently, we utilized stochastic frontier analysis and trade inefficiency analysis to investigate the factors associated with the export value across 182 countries and regions from 2020 to 2022. The export value data was sourced from the China Chamber of Commerce for Import and Export of Medicines and Health Products. The associated factors were sourced from publicly available databases. Results Joinpoint regression analysis showed the Annual Average Percent Change (AAPC) of the export value of traditional Chinese medicinal products from 2013 to 2022 was 6.9211 (95% Confidence Interval [CI] 5.9176 to 7.9341). Among them, raw material-based products included Chinese medicinal materials and herbal decoction pieces, as well as plant extracts, with AAPC being 1.7822 (95%CI −3.4203 to 7.2649), and 10.0290 (95%CI 3.5599 to 16.9023), respectively. They comprised over 80% of total exports. High value-added products included Chinese patent medicines and TCM health products, with AAPC being 3.6420 (95%CI −0.7595 to 8.2387) and 17.0895 (95%CI 4.7468 to 30.8865), respectively. They constituted a relatively minor share of total exports. Stochastic frontier analysis showed the coefficient (t-ratio) of factors associated with the export, including China’s GDP at 0.0772 (9.3276), the GDP of the export country or region at 0.1240 (3.9521), the capital distance between the export country or region and China at −0.3059 (−8.2793), the population of the export country or region at 0.0329 (3.4657), having a common border with China at −0.3179 (−4.3428), having a common language with China at 1.3316 (13.3217), being a landlocked country or region at −0.3531 (−9.3519). Trade inefficiency analysis showed the coefficient (t-ratio) of associated factors, including having a trade agreement with China at −7.1587 (−38.7960), pharmaceutical products tariffs at 0.2930 (7.7920), cultural distance from China at 0.5995 (7.1274), the overseas registration status of Chinese patent medicines at 2.3608 (13.6945), and the presence of TCM institutions at 6.1643 (16.1009). Conclusions The export value of traditional Chinese medicinal products from 2013 to 2022 showed an overall upward trend. However, the export structure remained suboptimal. Stochastic frontier analysis and trade inefficiency analysis revealed the relevance of associated factors to the export value. Based on the above results, we recommend six measures to optimize the export structure and enhance the international recognition of traditional Chinese medicinal products.